2022
DOI: 10.1016/j.adro.2022.100904
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Androgen Deprivation Use in Men With Intermediate-Risk Prostate Cancer Who Underwent Radiation Therapy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It was possible that similar changes in the selection of patients for ADT have influenced the cardiovascular outcomes. This was especially relevant since the use of ADT is heavily dependent on patient preferences even within guidelines [ 3 , 22 ], with studies having shown significant variations in practice [ 23 , 24 ]. It may thus be reasonable to speculate that changes in patient preferences outside the scope of this study may have contributed to the differences in cardiovascular burden and outcomes, either directly or by influencing patient selection for ADT.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible that similar changes in the selection of patients for ADT have influenced the cardiovascular outcomes. This was especially relevant since the use of ADT is heavily dependent on patient preferences even within guidelines [ 3 , 22 ], with studies having shown significant variations in practice [ 23 , 24 ]. It may thus be reasonable to speculate that changes in patient preferences outside the scope of this study may have contributed to the differences in cardiovascular burden and outcomes, either directly or by influencing patient selection for ADT.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of men who receive ADT is 68–69 years old, 18 with ADT increasingly prescribed for longer durations (≥24 months) based on evidence of improved disease‐free status and overall survival even in higher risk PCa 19 . This highlights the importance of understanding interactions of long‐term ADT with age‐related cognitive decline that is most pronounced at or after age 65.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 As a result, the use of ADT in PCa has been investigated for its effects on cognition and the brain, showing relationships with lower cognitive performance, higher risk of dementia, 13 as well as reductions in gray matter volume, 14 white matter integrity, 15 and compensatory restingstate functional activity. 16,17 The median age of men who receive ADT is 68-69 years old, 18 with ADT increasingly prescribed for longer durations (≥24 months) based on evidence of improved disease-free status and overall survival even in higher risk PCa. 19 This highlights the importance of understanding interactions of long-term ADT with age-related cognitive decline that is most pronounced at or after age 65.…”
Section: Introductionmentioning
confidence: 99%
“…However, the benefit may vary for individuals within each risk group, and treatment decisions require understanding the patient's individual risks, goals, preferences, and willingness to undergo various therapies. For example, only 53% of patients with unfavorable intermediate-risk prostate cancer who received RT between 2004 and 2016 added ADT, 20 although randomized trial data showed improved outcomes as early as 2002. 21 An accurate prognostic estimate of the baseline risk is necessary to determine an individual's ARR.…”
Section: Introductionmentioning
confidence: 99%